Bioequivalence study of levofloxacin tablets in healthy Indian volunteers using HPLC - Das, Ayan; Mukherjee, Jayanti; Dey, Goutam; Sarkar, Amlan K; Sahoo, Bijoy K; Chakrabarty, Uday S; Nandi, Utpal; Pal, Tapan K (Arzneimittelforschung, 2011)
An improved HPLC method was developed and validated for the determination of concentration of levofloxacin (CAS 100986-85-4) in human plasma. This paper is an attempt to compare the bioavailability of two levofloxacin tablet formulations (reference and test) containing 500 mg of levofloxacin. Both the formulations were administered orally as a single dose, separated by a washout period of 1 week. The HPLC method was validated by examining the precision and accuracy for the inter-day and intra-day runs in a linear concentration range of 0.10–10.00 μg/ml. Bioequivalence of two formulations were determined in 12 healthy, Indian, male volunteers in a single-dose, two-period, two-sequence, two-treatment crossover study. The content of levofloxacin in plasma was determined using HPLC with UV detection.The formulations were compared using the following pharmacokinetic parameters: area under the plasma concentration-time curve (AUC0–t), area under the plasma concentration-time curve from zero to infinity (AUC0–∞), peak plasma concentration (Cmax), and time to reach peak plasma concentration (tmax). The results indicated that there were no statistically significant differences (P > 0.05) between the logarithmically transformed AUC0–∞ and Cmax values of the test and reference formulations. The 90% confidence interval for the ratio of the logarithmically transformed AUC0–t, AUC0–∞ and Cmax were within the bioequivalence limit of 0.8–1.25 and the relative bioavailability of the test formulation was 99.98% of that of the reference formulation.
Keywords: Antibacterial; CAS 100986-85-4; HPLC-UV; Levofloxacin; Pharmacokinetics